Elemental signatures in bone to determine life history characteristics in fish. - Clarke, Adrian D. (Author); Shrimpton, Mark (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2005)
We used Laser-Ablation-Inductively-Coupled-Plasma-Mass-Spectrometry (LA-ICP-MS) to determine if trace metals deposited in calcified structures could be used to infer the life histories of three different species of fish. We were successful in resolving the movements and age at maturity for an anadromous species, the eulachon ('Thaleicthys pacificus') using both Strontium (Sr):Calcium (Ca) and Barium (Ba):Calcium ratios deposited in otoliths. Stream of residence was identified for a non-migratory freshwater species, the slimy sculpin ('Cottus cognatus') in the Williston Reservoir by matching the chemical fingerprint measured in the otolith to the water chemistries where they were captured. We could not reveal, however, movement of bull trout ('Salvelinus confluentus') in the Morice River watershed. Water chemistry was similar throughout the length of the Morice River and movements within the mainstem of this river, therefore could not be distinguished. We conclude that chemical ratios measured in calcified structures are useful for quantifying life-history in fish providing that sufficient differences exist in the fishes ambient chemical environment. 1Clarke, A. D., Shrimpton, J. M., and Telmer, K. are all contributing authors for: Chapter 2 Life History and Patterns of Movement Between Fresh- and Seawater in Eulachon ('Thaleicthys pacificus'); Chapter 3 Discrimination of Habitat use by Slimy Sculpins ('Cottus cognatus') in Tributaries of the Williston Reservoir using Natural Elemental Signatures; Chapter 4 Movement Patterns of Bull Trout (' Salvelinus confluentus') in the Morice Watershed using Chemical Signatures Deposited Spatially in Fin Rays. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1285106